Publishing for the popes : the Roman Curia and the use of printing (1527-1555) - Sachet, Paolo (Library of the written word. Handpress world, 2020)
"In this book Paolo Sachet provides a detailed account of the attempts made by the Roman Curia to exploit printing in the mid-sixteenth century, after the Reformation but before the implementation of the ecclesiastical censorship. Conventional wisdom maintains that Protestant exploitation of printing was astute, active and forward-looking, whereas the papacy was inept, passive and reactionary in dealing with the relatively new medium of communication. Publishing for the Popes aims to provide an impartial assessment of this assumption. By focusing on the editorial projects undertaken by members of the Roman Curia between 1527 and 1555, Sachet examines the Catholic Church's attitude towards printing, exploring its biases and tactics"--